Numerical and experimental investigation of dielectric recovery in supercritical N2. (5th February 2015) - Zhang, J; Markosyan, A H; Seeger, M; van Veldhuizen, E M; van Heesch, E J M; Ebert, U
Abstract: A supercritical (SC) nitrogen (N2 ) switch is designed and tested. The dielectric strength and recovery rate of the SC switch are investigated by experiments. In order to theoretically study the discharge and recovery process of the SC N2 switch under high repetition rate operation, a numerical model is developed. For SC N2 with initial parameters of p = 80.9 bar and T = 300 K, the simulation results show that within several nanoseconds after the streamer bridges the switch gap, the spark is fully developed and this time depends on the applied electric field between electrodes. During the whole discharge process, the maximum temperature in the channel is about 20 000 K. About 10 µ s after the spark excitation of 200 ns duration, the temperature on the axis decays to T axis ⩽ 1500 K, mainly contributed by the gas expansion and heat transfer mechanisms. After 100 µ s, the dielectric strength of the gap recovers to above half of the cold breakdown voltage due to the temperature decay in the channel. Both experimental and numerical investigations indicate that supercritical fluid is a good insulating medium that has a proved high breakdown voltage and fast recovery speed.